PP.20.25: EVALUATION OF MACROVASCULAR FUNCTION IN A POPULATION OF RHEUMATIC PATIENTS AND MATCHED CONTROLS. (June 2015) - Anyfanti, P.; Triantafyllou, A.; Pyrpasopoulou, A.; Triantafyllou, G.; Botis, I.; Chatzimichailidou, S.; Gkaliagkoysi, E.; Aslanidis, S.; Douma, S.
Abstract : Objective: Patients suffering from rheumatic diseases are characterized by increased cardiovascular risk, demonstrated by elevated rates of cardiovascular morbidity and mortality. Although systemic inflammation and autoimmune-mediated atherosclerosis have been identified as potential contributors, their impact on macrovascular function remains under intense investigation, with available studies often demonstrating conflicting results. Design and method: The aim of the present study was to evaluate macrovascular function in consecutive patients with rheumatoid arthritis attending a rheumatology outpatient clinic, and compare the status of the macrovasculature with individuals matched for age, sex, blood pressure and cholesterol levels. Arterial stiffness was evaluated with measurement of carotid-femoral pulse wave velocity (PWV), which was assessed by use of applanation tonometry (Sfygmocor device). Carotid ultrasound was used for the measurement of mean carotid intima-media thickness (cIMT). Results: A total of 132 individuals, 28 males and 104 females, were included in the study. Of them, 61.4% were suffering from rheumatoid arthritis, 6.8% from systemic sclerosis, 2.3% from systemic lupus erythematosus, while the rest 29.5% comprised the control population. Rheumatic patients were matched to controls in terms of age (60.3 ± 13 versus 57.4 ± 8.1 years, p = 0.147), sex (19.4% versus 25.6% males, p = 0.420), systolic blood pressure (123.7 ± 15 versus 122.3 ± 11.7 mmHg, p = 0.614), diastolic blood pressure (74.7 ± 10 versus 77.0 ± 7.9 mmHg, p = 0.187), body mass index (26.5 ± 5.3 versus 27.1 ± 4.4, p = 0.510), smoking status (28.4% versus 33.3%, p = 0.656) and total cholesterol levels (204.9 ± 38.2 versus 214.5 ± 38.5 mg/dl, p = 0.249). Mean PWV in rheumatic patients significantly differed compared to controls (8.4 ± 2.2 versus 7.3 ± 1.2, p = 0.010). Likewise, mean cIMT was significantly higher in rheumatic patients compared to controls (0.69 ± 0.13 versus 0.62 ± 0.09 mm, p = 0.026). Conclusions: Patients suffering from rheumatic diseases exhibit significantly higher levels of both arterial stiffness and cIMT compared to well-matched controls. This difference appears to be independent of blood pressure and other cardiovascular risk factors. This is one of the few studies simultaneously assessing indices of macrovascular function in patients with rheumatic diseases, compared to well-matched controls. Further studies are needed to clarify to which extent macrovascular damage in these patients contributes to their increased cardiovascular morbidity and mortality, independent of traditional cardiovascular risk factors.